ERP Evidence for Inhibitory Control Deficits in Test-Anxious Individuals - Zhang, Wenpei; De Beuckelaer, Alain; Chen, Lirong; Zhou, Renlai (Frontiers in Psychiatry, 2019)
The cognitive mode describing an assessment (test) as a potential threat as observed in individuals high versus low in test anxiety (i.e., HTA versus LTA) may reveal how this cognitive mode may cause and maintain anxiety through its impact on the individual’s ability of inhibitory control. The present experimental study (with ERP data), which relies on both an emotional stroop task (ES) and a numerical stroop (NS) task examines the nature of this impact, but separately for cases of test-related and cognitive interference. Results show that HTA have extensive inhibitory deficits (see P3) and make an effort to compensate for decreased efficiency. HTA were successful in this effort in case of cognitive interference, but unsuccessful in case of test-related interference; being unsuccessful was due to the excessive attentional resources required to automatically process the relevant stimuli (see P1-P2-N2 only in ES). Additionally, HTA are cautious in that they try to maintain accuracy when completing the ES and NS tasks, and even by sacrificing on efficiency in ES. ES results also show that the degree of emotional interference indicates the level of an individual’s anxiety, and the P2 may serve as an index of the level of test anxiety.